POTENSI ANTIMIKROBA EKSTRAK ETANOL SARANG SEMUT (Myrmecodia tuberosa Jack.) TERHADAP Candida albicans, Escherichia coli DAN Staphylococcus aureus - Yuli Nurullaili Efendi; Triana Hertiani (Majalah Obat Tradisional, 2013)
The importance of finding a new natural source of antiinfective compounds has urged a research to explore antimicrobial activity of Ant-Plant (M. tuberosa) ethanol extract. This particular plant has been widely used in West Papua as part of traditional remedy. This research aimed to explore the antimicrobial potency of Ant-Plant ethanol extract against C. albicans, E. coli and S. aureus and to characterize the active compound group responsible for the activity.  Dried powders were macerated in ethanol 70%, followed by evaporating the solvent. The extract was screened for antimicrobal activity against C. albicans, E. coli, and S. aureus by disc difussion method. A micodillution assay was performed to find out the MIC values, followed by MBC value determination in suitable solid media. Bioautography contact method was used to detect the antimicrobial active spots. The result revealed the extract’s MIC values against C. albicans, E. coli, and S. aureus were 0.8% w/v; 0.8% w/v; and 1.6% w/v respectively. MBC values were >6.4% w/v against C. albicans, 6.4% w/v against E. coli and 1.6% w/v against S. aureus. Active spot against E. coli and S. aureus shown by bioautography test results had hRf 0 (silica gel 60 F254, toluene: acetone: methanol: formic acid (26:8:5:1) v/v) while hRf 53 spot was active against C. albicans and S. aureus and detected as phenolic. It was concluded that the M. tuberosa ethanol extract contained active compounds which were potential to be developed as antimicrobial agent especially S. aureus.